Rancang Bangun Alat Pengemas Petis Udang Guna Mengurangi Waktu Proses Produksi dengan Pendekatan Antropometri - Ananta, Fachrezi Pramudia; Herlina, Herlina (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
The manual packaging process at the "Lia Jaya" shrimp paste SME in Surabaya takes approximately 1 minute and 42 seconds per jar, affecting production efficiency and causing delays in deliveries to resellers. With a daily production capacity of 60–70 kg or 1,440 jars per week, manual packaging has become a significant obstacle in meeting the increasing market demand. This study aims to design and develop an automated shrimp paste packaging machine to reduce production time, enhance efficiency, and ensure product safety. The research methodology involved collecting anthropometric data from operators, analyzing work time, designing a tool based on ergonomic principles, and testing its performance. The designed machine automates the packaging process, reducing packaging time by up to 40%, while producing more uniform, hygienic, and high-quality packaging. Additionally, this machine reduces dependence on manual labor and allows workforce allocation to other production processes. The study results indicate that the machine not only increases the productivity of the "Lia Jaya" shrimp paste SME but also serves as an innovative solution for similar SMEs. This tool supports product competitiveness in both local and national markets. Keywords: Automatic Packaging, Efficiency, Ergonomics, Productivity